Corporate Governance and Environmental Disclosure in the Indonesian Mining Industry - Terri Trireksani; Hadrian Geri Djajadikerta (Australasian Accounting, Business and Finance Journal, 2016)
Sustainability and corporate governance issues are now considered to be important and integral aspects of company performance. Both have established themselves as well-studied topics in the organisational and accountability areas. While there has been a growing interest to study the relationship between these two areas, research publication in this topic is still mainly focused on the Western societies. This study focuses on the corporate governance and sustainability disclosure practices in one of the emerging economies, Indonesia, and assesses the relationships between corporate governance variables and the extent of environmental disclosures made by the mining companies listed in the Indonesia Stock Exchange (IDX) in their annual reports. The main findings of this study show that the extent of environmental disclosure made by these companies was moderate, and that there is a significant positive relationship between the size of board of directors and the extent of environmental disclosure.
Keywords: Corporate governance; Environmental disclosure; Mining industry; Indonesia